Congenital Midline Cervical Cleft: First Report and Genetic Analysis of Two Related Patients. (July 2020) - Masood, Maheer M.; Mieczkowski, Piotr; Malc, Ewa P.; Foreman, Ann Katherine M.; Evans, James P.; Clark, J. Madison; Rose, Austin S.
Objectives: Congenital midline cervical cleft (CMCC) is a rare congenital anterior neck anatomical anomaly. We present the case of two related patients (grandchild and maternal grandmother) who were both born with a congenital midline cervical cleft along with genetic analysis. Methods: Clinical examination of both patients and surgical excision of the grandchild was performed. Genetic analysis with exome sequencing (ES) was conducted for both patients. Results: Genetic analysis with exome sequencing (ES) revealed apparently novel single nucleotide variants in 66 genes present in both proband and grandmother. Five of these variants are predicted to cause frameshifting in the coding region of the respective genes and truncated proteins ( OVGP1, TYW1B, ZAN, SSPO, FOLR3 ). Two of these genes ( TYW1B and SSPO ) have homozygous indel mutations in both patients. Conclusions: To our knowledge, this is the first case of two related patients with a congenital midline cervical cleft. The results of our genetic analysis reveal potential relevance to CMCC development.